Diagnostic criteria, clinical characteristics, and natural history of Cohen syndrome. Issue 4 (1st April 2003) - Chandler, K E; Kidd, A; Al-Gazali, L; Kolehmainen, J; Lehesjoki, A-E; Black, G C M; Clayton-Smith, J
Abstract : Cohen syndrome is a rare, recessively inherited condition associated with facial dysmorphism, developmental delay, and visual disability. A delay in making the diagnosis commonly occurs, contributed to by the lack of a definitive molecular test and the clinical variability of published case reports. A specific clinical phenotype has been delineated in a homogeneous cohort of Finnish Cohen syndrome patients, but the applicability of their diagnostic criteria to non-Finnish patients has been debated. Detailed delineation of Cohen syndrome in patients from outside Finland is therefore warranted. We report on the clinical features of 33 non-Finnish Cohen syndrome patients. Variability within the clinical spectrum is identified and the natural history of Cohen syndrome described. Diagnostic guidelines for facilitating accurate and early diagnosis are discussed. Results from molecular genetic analysis using markers located within the previously mapped COH1 critical region support allelic but not genetic heterogeneity in this UK cohort.